The oral health behaviours and fluid consumption practices of young urban Aboriginal preschool children in south‐western Sydney, New South Wales, Australia. (30th January 2018) - George, Ajesh; Grace, Rebekah; Elcombe, Emma; Villarosa, Amy R.; Mack, Holly A.; Kemp, Lynn; Ajwani, Shilpi; Wright, Darryl C.; Anderson, Cheryl; Bucknall, Natasha; Comino, Elizabeth
Abstract: Issue addressed: Australian Aboriginal children have a higher risk of dental caries yet there is limited focus on oral health risk factors for urban Aboriginal preschool children. This study examined the oral health behaviours and fluid consumption practices of young children from an urban Aboriginal community in south‐western Sydney, Australia. Methods: In total, 157 Aboriginal children who were recruited to the "Gudaga" longitudinal birth cohort participated in this study. A survey design was employed and parents responded to the oral health questions when their child was between 18 and 60 months. Results: Few parents (20%) were concerned about their child's oral health across the time period. By 60 months, only 20% of children had seen a dentist while 80% were brushing their teeth at least once daily. High levels of bottle use were seen up to 30 months. Consumption of sugary drinks was also very high in the early years, although this was replaced by water by 36 months. Conclusions: While there are some encouraging findings, such as the rates of tooth brushing and increasing rates of water consumption, the findings do highlight the poor uptake of dental services and high levels of bottle usage among urban aboriginal children during their early years. So what?: Targeted oral health promotional programs are needed in the urban Aboriginal community to better support parents understanding of good oral health practices in the early years and engagement with dental health services.